ANALISIS PERBANDINGAN KINERJA PERUSAHAAN SEBELUM DAN SESUDAH MENGADAKAN EMPLOYEE STOCK OWNERSHIP PROGRAM (ESOP) (Study Kasus Pada Perusahaan yang Menerapkan ESOP) - Nurhidayati Nurhidayati; Anik Malikah; Afifudin Afifudin (Universitas Islam Malang, 2019)
ABSTRACTThis study is conducted to see whether there are any differences in company performance before and after holding an Employee Stock Ownership program (ESOP) in 2016. The sample in this study is data from non-financial companies that made the announcement of the Employee Stock Ownership Program (ESOP) for the period 2014 to 2018. The analytical method used is the paired sample T-test. Based on the results of the analysis that has been carried out, the comparative Analysis of Company Performance Before and After Adopting the Employee Stock Ownership Program (ESOP), it can be concluded that there is no significant difference in the Comparison of Company Performance analysis Before and After Adopting an Employee Stock Ownership Program (ESOP). In this study there were 4 samples. This is measured by financial ratios, namely, Net Profit Margin (NPM), Return On Assets (ROA), Total Assets Turn Over (TATO). While the Return On Equity Ratio (ROE) stated there were significant differences in the Comparison of Company Performance Analysis Before and After Adopting an Employee Stock Ownership Program (ESOP).Keywords: Net Profit Margin (NPM), Return On Assets (ROA), Total Assets Turn Over (TATO), Return On Equity Ratio (ROE).